Pengaruh algoritma filter bubble dan echo chamber terhadap perilaku penggunaan internet - Virani Wulandari; Gema Rullyana; Ardiansah Ardiansah (Perpustakaan Universitas Gadjah Mada, 2021)
Introduction. This study aims to explore effects of bubble filter and echo chamber on information searching behaviour on the internet, how it affects the scope of the internet ecosystem and users, and what we can see from the behaviour. Data Collection Method. The paper used a mixed-methods approach with surveys, online discussions, and literature research. Twenty respondents between 19-21 years old participated in this exploratory study. Analysis Data. Data was obtained and calculations have automatically accumulated through Google Form. The user data analysis and discussion were conducted manually by considering aspects of rationality concerning the literature and previous research. Results and Discussions. The analysis results obtained were bubble filter and echo chambers were proven to affect internet users both in positive and negative ways. Conclusions. Bubble filter and echo chamber may have both positive and negative effects simultaneously, however, it depends on the user because the system has provided control features to reduce both features. Using internet wisely is also parts of the important aspect.